2013
DOI: 10.1007/978-3-642-36981-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Intelligent Decision Support System – Technology Acceptance in Intensive Care Units

Abstract: Intensive Care Units are considered a critical environment where the decision needs to be carefully taken. The real-time recognition of the condition of the patient is important to drive the decision process efficiently. In order to help the decision process, a Pervasive Intelligent Decision Support System (PIDSS) was developed. To provide a better comprehension of the acceptance of the PIDSS it is very important to assess how the users accept the system at level of usability and their importance in the Decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The BI platform for the VIP unit in CMIN is based on the Web following pervasive characteristics (Filipe Portela, Jorge Aguiar, Manuel Filipe Santos, Álvaro Silva, & Fernado Rua, 2013;C. F. Portela, Santos, Silva, Machado, & Abelha, 2011;F.…”
Section: Business Intelligence Platform For Vipmentioning
confidence: 99%
“…The BI platform for the VIP unit in CMIN is based on the Web following pervasive characteristics (Filipe Portela, Jorge Aguiar, Manuel Filipe Santos, Álvaro Silva, & Fernado Rua, 2013;C. F. Portela, Santos, Silva, Machado, & Abelha, 2011;F.…”
Section: Business Intelligence Platform For Vipmentioning
confidence: 99%
“…One of its goals is to make their job in a pervasive way [15,16]. INTCare [18] was an important trigger to develop an intelligent environment. The environment is now prepared to identify critic events and support the system developed in real-time.…”
Section: Intcarementioning
confidence: 99%
“…The questionnaire was answered by 1/3 of ICU nurses and in a 5 points scale (1-worst; 5 -excellent) had an average upper than 3 points. The questionnaires results [25] showed that the information generated (knowledge) and the system deployed are very important to the ICU professionals, being them suitable and framed in the decision making process.…”
Section: Fig 6 Intcare Prediction Systemmentioning
confidence: 99%